Atherosclerosis as a cause of death in patients with cancer: a cohort study - Ramez M. Odat; Sakhr Alshwayyat; Dang Nguyen; Tala Abdulsalam Alshwayyat; Hanan M. Qasem; Hritvik Jain; Hamdah Hanifa; Osama Aloudat; John C. Lin; Wilfred Ngwa; Margaret E. G. Thompson; Amer Harky (Cardio-Oncology)
Abstract Introduction Non-cancer deaths are now becoming a significant threat to the health of cancer patients. Death from atherosclerosis is linked to cancer due to the side effects of treatment and its pathogenesis. However, guidelines for identifying cancer patients at the highest risk of death from atherosclerosis remain unclear. In this study, we aimed to identify the correlation between various outcomes and the risk of death from atherosclerosis as well as to determine which cancer subtypes are linked to a higher risk of mortality from atherosclerosis. Methods Data of all patients diagnosed with cancer between 2000 and 2021 were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Data regarding the causes of death and clinicopathological features such as sex, age, race, marital status, SEER stage, and treatment procedures were extracted. We calculated standardized mortality ratios (SMRs) using the SEER*Stat software V8.4.3. Results Of the 6,891,191 cancer patients, 3,900 (0.057%) died of atherosclerosis, a rate higher than that in the general population (SMR = 1.18, 95% CI [1.15–1.22]). Atherosclerosis-related deaths decreased over time from 1,882 deaths between 2000 and 2004 to 279 deaths between 2015 and 2019. Among the 3,900 atherosclerotic deaths, the highest numbers were observed in patients with digestive cancers (n = 768, 19.7%), particularly colon and rectal cancer (n = 544, 13.9%), prostate cancer (n = 742, 19%), and breast cancer (n = 544, 13.9%). Patients with brain cancer (SMR = 4.96, 95% CI [3.07–7.59]), liver and intrahepatic bile duct cancers (SMR = 3.20, 95% CI [2.24–4.43]), and pancreatic cancer (SMR = 2.69, 95% CI [1.97–3.59]) had a significantly higher rate of death from atherosclerosis than the general population. Conclusion Our study revealed a higher atherosclerosis mortality risk among patients with cancer in the United States, emphasizing the need for integrated care that addresses cancer and cardiovascular risks to improve overall patient outcomes. However, our conclusions are restricted to the aggregated data provided by SEER, and we encourage future studies to explore more detailed datasets.